Task-shifting to optimize outpatient neurological care in Zambia - Ana C. Villegas; Deanna Saylor; Michelle Kvalsund; Masharip Atadzhanov; Clarence Chiluba; Lorraine Chishimba; Stanley Zimba; Mashina Chomba; Omar K. Siddiqi (BMC, 2021)
Abstract Objective To investigate opportunities for task shifting to decongest an outpatient neurology clinic in Zambia by describing current patient flow through the clinic and potential nodes for intervention using process mapping. Background Zambia has a population of approximately 18 million people with 4 full-time adult neurologists, as of 2018, who all practice at the University Teaching Hospital (UTH), the main tertiary care center in the country. As a result of this provider-to-patient ratio, the outpatient neurology clinic is overcrowded and overbooked. Task-shifting programs have shown to improve efficiency, access and quality of care through the use of less specialized healthcare workers in low- and middle-income countries (LMIC). Methods We evaluated patient flow in the UTH neurology outpatient clinic through the development and analysis of a process map. The characteristics of the clinic population between 2014 and 2018 were retrospectively reviewed from the clinic register. Between July and August 2018, we prospectively collected appointment lag times and time each patient spent waiting at various points in the clinic process. We conducted interviews with clinic staff and neurologists to generate a detailed process map of current pathways to care within the clinic. We then devised task-shifting strategies to help reduce patient wait times based on the overview of clinic process mapping and patient demographics. Results From 2014 to 2018, there were 4701 outpatients seen in the neurology clinic. The most common neurological diagnoses were epilepsy (39.2%), headache (21.5%) and cerebrovascular disease (16.7%). During prospective data collection, patients waited an average of 57.8 (SD 73.4) days to be seen by a neurologist. The average wait time from arrival in the clinic to departure was 4.0 (SD 2.5) h. The process map and interviews with clinic staff revealed long waiting times due to a paucity of providers. Nurses and clerks represent an influential stakeholder group, but are not actively involved in any activity to reduce wait times. A large proportion of follow-up patients were stable and seen solely to obtain medication refills. Conclusions Epilepsy, headache, and stroke make up the largest percentage of outpatient neurological illness in Zambia. Targeting stable patients in these diagnostic categories for a task-shifting intervention may lead to substantially decreased patient wait times. Potential interventions include shifting clinical follow-ups and medication refills to less specialized healthcare workers.